Efficient charge separation between ZnIn2S4 nanoparticles and polyaniline nanorods for nitrogen photofixation. (24th April 2020) - Chen, Shaohua; Zhao, Xiaoli; Xie, Fazhi; Tang, Zhi; Wang, Xiufang
Abstract : Novel core–shell polyaniline@ZnIn2 S4 core–shell heterostructure photocatalysts have been prepared using a simple synthesis process, and they exhibit superior performances of photocatalytic N2 reduction to NH3 in an atmospheric environment. Abstract : Here, novel core–shell polyaniline@ZnIn2 S4 (PANI@ZnIn2 S4 ) heterostructure photocatalysts have been prepared using a simple synthesis process, and the ZnIn2 S4 nanoparticles grow directly on the surface of PANI nanorods through strong interactions between the two semiconductors. The PANI@ZnIn2 S4 heterostructure composites show extraordinary photocatalytic effects for the reduction of nitrogen in a natural environment. The PANI@ZnIn2 S4 (ZnIn2 S4 15 wt%) composite reveals the highest catalytic activity, and the maximum efficiency for ammonia generation can reach 290 μmol L −1 h −1, which is 10.3 times as high as that of pure ZnIn2 S4 . This superior photocatalytic performance of PANI@ZnIn2 S4 is ascribed to the increased light absorption capacity, rich reactive sites and strong nitrogen activation ability. In particular, the efficient interfacial interactions between the ZnIn2 S4 nanoparticles and PANI nanorods facilitate the separation and transfer of photogenerated electrons and holes. This work provides an effective approach to construct novel photocatalytic systems for efficient photocatalytic nitrogen fixation.